Pengaruh Dosis Konsorsium Pupuk Hayati dan Dosis Nutrisi terhadap Populasi Bakteri Pelarut Fosfat dan Hasil Tomat (Solanum lycopersicum L.) pada Sistem Hidroponik - Iva Fitriani; Pujawati Suryatmana; Emma Trinurani Sofyan (Soilrens, 2017)
Hydroponic system is an alternative agricultural cultivation technology that able to answer the problem of narrowing farmland, decline in soil fertility, and the need of healthy foods. Production of tomato with this system has its own market segment, but it needs a specific treatment, such as preparation of planting medium, usage of fertilizer and addition of nutrient, etc. This experiment aims to determine the effect of biofertilizer consortium dosage and nutrient dosage, as well as their interaction to the population of phosphate solubilizing bacteria and tomato yield. The experiment was conducted in a greenhouse of Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, in June to October 2015. Design of experiment was arranged in factorial randomized block design consisting of two factors. The first factor was biofertilizer consortium dosage (0 mL/polybag, 5 mL/polybag, and 10 mL/polybag), and the second factor was nutrient dosage (0 mL, 250 mL, and 500 mL). The result showed that there was no interaction between biofertilizer consortium dosage and nutrient dosage to the population of phosphate solubilizing bacteria and tomato yield.ywords: biofertilizer consortium, hydroponic, phosphate solubilizing bacteria, tomato